Kegiatan Keagamaan Majelis Taklim Al-Husna Tuan Guru H Muhammad Rasyid Ridho dan Dampaknya Terhadap UMKM di Komplek Lutfia Kecamatan Gambut - Nur Habibah; Rahmah Rahmah; Sri Anafarhanah (UIN Antasari Banjarmasin, 2022)
This study aims to describe the implementation of the religious activities of the Al-Husna Taklim Assembly Tuan Guru H Muhammad Rasyid Ridho and their impact on MSMEs in the Lutfia complex, Gambut District. This research is a field research with a descriptive qualitative approach. Data collection was carried out by observation and interview techniques. The results of this study indicate that the implementation of MSME activities in the Religious Activities of the Al-Husna Taklim Assembly is carried out on the basis of interaction and motivation which are managed individually and in groups. The implementation of the Taklim Assembly has had a positive impact on MSMEs both for MSME actors and congregations such as: making it easier for congregations to get their daily needs and increasing the income of MSME players because the number of congregations continues to grow.